Spatial Design Makes a Difference in Student Academic Engagement Levels: A Pilot Study for Grades 9-12 - Scott-Webber, Lennie; Konyndyk, Roger; French, Raechel; Lembke, Jason; Kinney, Taryn (European Scientific Journal, ESJ, 2017)
Our research question was, ‘Can we demonstrate that the design of the built environment for grades 9-12 impacts student academic engagement levels?’ A pilot study was conducted using a convenience sample, a high school (grades 9-12) in the USA’s mid-west with a four-year old design solution. To answer the question we designed two online survey instruments, one for students and one for educators, enabling us to construct engagement indexes for each. We then correlated the level of self-reported engagement, as measured by our indexes, with the perceptions of the built environment. A mixed-methodology research technique was used for this research project. Focused interviews used K-12 architects (n=6), administrators (n=3), teachers (n=35), students (n=25). A fifteen (15) question ‘Alpha’/pilot survey was then designed, developed, pre-tested and then submitted to the full membership of the school. Findings revealed that both students and educators agreed that the design of the built environment makes a difference relative to their engagement at both the macro (i.e., Overall) and micro (i.e., Classrooms) at a high level of significance (p<.0001); spatial design makes a difference. The survey proved to be both reliable and valid. Finally, we pay particular attention to questions relating to “movement” and learning.